Developing Reading Materials Based on Mandailing Folktales to Increase Children's Interest in Literacy - Rahmi Wahyuni; Ardina Khoirun Nisa; Elismayanti Rambe (Civiliza Publishing, 2026)
This article discusses the development of reading materials based on Mandailing folktales as a strategy to increase children's interest in literacy. Folktales are an important part of local culture, containing educational and moral values. However, children in the Mandailing region still have low interest in reading, which can hinder their literacy development. Through this community service, we strive to create reading materials that are engaging and relevant to the local culture, thereby capturing children's attention. This activity includes collecting and adapting Mandailing folktales, developing engaging reading materials, and conducting literacy workshops for children. By involving the local community, we hope to raise awareness of the importance of literacy and local culture. Results from this activity indicate that children are more enthusiastic about reading when the reading materials presented relate to stories they know and love. Furthermore, this activity provides an opportunity for parents and educators to play an active role in supporting children's reading interests. Thus, the development of reading materials based on Mandailing folklore serves not only as a tool to increase literacy interest but also as an effort to preserve local culture. It is hoped that this initiative can serve as a model for other regions in developing children's literacy through an approach based on local wisdom.